Validity of computed tomographic in assessment of genial tubercle and anterior mandible as a reference guide to locate osteotomy in genioglossus advancement - Kadem, Hanan J; Fatah, Ahlam A (Journal of Baghdad College of Dentistry, 2014)
Background: Genioglossus advancement is a surgical procedure to advance the tongue in some patients with obstructive sleep apnea syndrome.The important step in this procedure is that of accurately capturing the bone segment attached to the genioglossus muscle to avoid complications such as mandibular fracture, devitalization of the inferior incisor roots, and incomplete incorporation of the genioglossus Materials and Method: Computed tomography scans were taken for 53 Iraqi adult patients (28 male and 25 female) range from (18-35) years with skeletal class I classification and intact anterior mandible dentition included in this study using sagittal and axial sections. The measurements were done for genial tubercle and anterior mandibular region. Results: The mean values of some measurements weresignificantly higher in males than in females. The effect of gender difference was evaluated as a strong effect. The mean value of the other measurements slightly higher among males compared to females, but the difference fail to reach the level of statistical significance. The effect of gender difference on this parameter was evaluated as a moderately strong effect.The results showed that there was no effect of age on all selected measurements in male and female. All selected measurements showed no statistically significant linear correlation with the age. Conclusions: The variable position and dimensions of this bone segment among patients suggest the need for CT before attempting genioglossus advancement for exact localization, avoiding the expected surgical complication